Haematinic potencies of the aqueous crude extracts of ficus mucoso and senna occidentalis in rabbits (2009)
A total of 20 domestic rabbits divided into 4 groups of 5 animals per group were used in this study to assess the haematinic potencies of the aqueous crude extracts of Ficus mucoso and Senna occidentalis and this was then compared with that of a proprietary haematinic, Haematopan B12®. Group A animals (control) were not bled but those in groups B, C and D were bled to induce anaemia. Group B animals were treated with Haematopan B12®, a commercially prepared haematinic, and groups C and D were treated with the aqueous crude extracts of Senna occidentalis (Linn) Link and Ficus mucoso Welw. ex Ficalho respectively. The post-haemorrhage treatment haematologic values were obtained at given intervals (7 days) and compared with the pre-haemorrhagic values earlier obtained. The study showed that all the experimental animals showed accelerated recovery since these animals had excellent response in terms of white blood cell (WBC) and its differentials, red blood cell (RBC) count, packed cell volume (PCV) and haemoglobin (Hb) concentration. Thus the extracts of Ficus mucoso and Senna occidentalis have comparative haematinic potencies as Haematopan B12®.